Controller changes and auditor changes - Guoqian Tu (China Journal of Accounting Research, 2012)
Using listed companies in China's A-share market from 1997 to 2009, this paper investigates the relationship between controller changes (including changes in controlling shareholders, directors and CEOs) and auditor changes. The empirical evidence indicates that controller changes are positively related to auditor changes and that auditor changes are more likely if there are extensive controller changes. For companies in which both the controlling shareholder and the auditor change, if the successor controlling shareholder is controlled by an other-province government, the auditor is more likely to be replaced and the successor auditor is more likely to be a smaller auditor from the same province as the new controlling shareholder.
Keywords: M42; 650; Controller changes; Auditor changes; Auditor choice